Validation of micellar LC-based methods applied to analyze foodstuffs. (February 2013) - Peris-Vicente, J; Carda-Broch, S; Esteve-Romero, J; Rambla-Alegre, M; Bose, D; Beltrán-Martinavarro, B; Marco-Peiró, Sergio; Martinavarro-Domínguez, A; Ochoa-Aranda, E; Chin-Chen, ML
The validation of several micellar LC-based analytical methodologies was described. These methods were able to quantify quinolones in fish from fisheries, hydroxytyrosol in olive extracts and biogenic amines in anchovy sauce. The validation was performed following the requirements of official guides to provide more reliability. Two guides suggested by renowned institution are described: US FDA Guidance for Industry and EU Regulation 2002/657/EC Decision. The appropriate guide was used for each method, depending of the analyte, the matrix and the scope of sample. The calculated validation parameters were those proposed by the guide: selectivity, calibration range, linearity, LOD and LOQ, inter- and intra-day accuracy and precision, limit of decision, detection capability, robustness, recovery and stability. The methodologies were successfully validated by the selected guideline, indicating their suitability to be applied to analysis of real samples, proven to be useful to its intended purpose.